Photosynthetic characteristics of geographically disjunct seaweeds: A case study on the early life stages of Antarctic and Subantarctic species - Navarro Martinez, Nelso Patricio; Huovinen, Pirjo; Gomez, Ivan (My University, 2019)
Propagules of geographically separated seaweeds distributed in both site of Antarctic Circumpolar Current are expected to show different light and temperature acclimation in order to cope with environmental condition in both Antarctic and Subantarctic regions. The objectives of this study were: (1) to compare the photosynthetic performance (rETR(max), E-k, and alpha(ETR)) of propagules of conspecific (Iridaea cordata and Adenocystis utricularis) and congeneric (Pyropia sp. and Monostroma sp.) seaweeds from Magellan strait (Subantarctic region) and King Gorge Island (Antarctica) using in vivo chlorophyll fluorescence techniques; and (2) to determine the physiological responses (measured by rapid adjustment of photochemistry, F-v/F-m) of tetraspores of L cordata from populations of both sites when exposed in laboratory to UV radiation. Differences in photosynthetic characteristics between propagules were observed in L cordata and Monostroma sp. while L cordata tetraspores from Subantarctic populations showed high light demands (E-k = 150 mu mol photon m (-2) s(-1)) when compared to those from Antarctic populations (E-k = 50 mu mol photon m(-2) s(-1)). Antarctic Monostroma sp. gametes exhibited higher E-k (300 mu mol photon M-2 s(-1)) than those of Subantarctic populations (130 mu mol photon m(-2) s(-1)). Antarctic tetraspores of I. cordata shown low inhibition in F-v/F-m (< 10%) after a 4-h exposure at 2 degrees C, while spores from Subantarctic population were more sensitive (> 60% inhibition) under similar exposure conditions. Similar as for other cold-temperate species, these differences appear to underlie biogeographical and evolutionary elements: in I. cordata, spores from Antarctica are more tolerant to UV at low temperatures than those from Subantarctic regions, but when exposed to increased temperature the detrimental effects of stress in tetraspores from both Antarctic and Subantarctic populations were ameliorated. This differential photosynthetic response to low temperature and light among algae with Antarctic and Subantarctic disjunction is an important ecophysiological attribute that can be associated with adaptations at a genetic level reported previously for some of these populations.
Keywords: Propagule; Dinoflagellate; Disjunct